Depiction of Substantial Radicalism and Women Enablement with Respect to Kiran Nagarkar’s Selected Novels (Integral Research, 2025)
In Indian English Literature, the place of Kiran Nagarkar is implausible and remarkable. Being a humanistic, he has represented the substantial feministic methodology for contemporary, profuse and liberated women. Though they encounter several peculiarities such as anguishes, deficiency, disorder, malnourishment, sorrow, bereavement, desperateness, estrangement, nervousness, unfairness, vehemence etc., still they fight with the catastrophes in a spirited manner. They never project themselves as repressed, troubled and downgraded characters. On the contrary, they convert their powerlessness, faintness and segregation into fitness, forte and annexation. Nagarkar demonstrates the social and copious womanlike aspects of female protagonists. It is noteworthy fact that the role of women is vivacious in society as well as in literature. In today’s universe, a contemporary woman is not restricted only for performing household chores but as an emancipated woman, she can demonstrate her worth and can outshine at compelling position like men. She has proved that she can support to her family and can work like men in this masculine dominated society. The researcher has projected radicalism, feminism and women enablement through Kiran Nagarkar’s some select novels such as: ‘Ravan & Eddie’ (1995), ‘The Extras’ (2012) and ‘Rest in Peace’ (2015). These fictional works depict the traits of feminine characters such as forte, individuality, consideration and audacity. Here the researcher has attempted to portray the genuine picture of the ‘female’ in radicalism and a ‘female’ in the contemporary world. In this research, the researcher has interpreted and analyzed the female characters and their traits and befit them in the frame of resilient and contemporary female in the Indian framework.
Keywords: Kiran Nagarkar, radicalism, women enablement, feminism, modern women, emancipation, self-governance, female characters.